PEMANFAATAN DAN DAMPAK BUDIDAYA KERAMBA JARING APUNG TERHADAP LINGKUNGAN DI KECAMATAN HARANGGAOL - Sri Fatimah; T. Syazanani; Mutiara Yusuf; Abdurrozzaq Hasibuan (Cross-border, 2023)
Lake Toba has a surface area of ​​approximately 1,132 km2 with a maximum depth of 529 m. Floating net cages (KJA) have a positive path as well as a negative path like two sides of a coin. In its development, the use of Lake Toba by the surrounding community has brought Lake Toba to various environmental problems. floating net cages (KJA) is an environmental management issue in Haranggaol District. Lake water quality has decreased due to residual fish feed (pellets) in the waters of Lake Toba caused by sedimentation of pollutants from domestic waste and food waste. This study aims to find out the benefits and impacts of floating net cage cultivation with the help of existing research works. This study used the literature review method found in the Google Scolar database. The results of this study are (KJA) as a source of income for the community and local revenue (PAD), but (KJA) as a very serious threat to the environmental ecosystem of Lake Toba considering the chemical pollution from fish feed in the KJA. The positive impact of the existence of (KJA) is that it can improve the economy in the people of Haranggaol District. The use of rusty dur and used drum oil has a huge impact on the environment, especially on abiotic depletion and toxicity due to nets containing carbolic elements, and so on. Saving ideas such as "zero cages" on Lake Toba need to be reconstructed into norms and culture that must be implemented by all parties.